Lower circulating mitochondrial DNA and increased mitokines suggest significant mitochondrial dysfunction in systemic lupus erythematosus with renal involvement - Camillo Ribi; Kristina Sundquist; Matthieu Halfon; Manuel Pascual; Ashfaque A Memon; Anna Hedelius (Lupus Science and Medicine)
Background SLE is associated with significant morbidity, especially in the case of renal involvement. Mitochondrial dysfunction plays a significant role in SLE and may be assessed by measuring mitochondrial DNA (mtDNA) and cytokines reflecting mitochondrial stress (mitokines). Circulating mtDNA is a promising biomarker in SLE and appears to be reduced in severe SLE. However, measuring circulating mtDNA is challenging and reported methods are heterogenous. Our study aimed at evaluating whole blood mtDNA to nuclear DNA (nucDNA) ratio using droplet-digital PCR and circulating mitokines, growth differentiation factor 15 (GDF-15) and fibroblast growth factor 21 in SLE with and without renal involvement.Methods Cross-sectional study involving 195 patients with SLE and age-matched healthy volunteers (HV) as control. Biomarkers were compared in patients with and without renal involvement (defined by estimated glomerular filtration rate <60 mL/min or proteinuria >0.5 g/day) and in those with active and inactive SLE.Results Compared with HV, patients with SLE displayed lower mtDNA/nucDNA ratios, especially in the case of renal involvement. Accordingly, mitokines were increased in patients with SLE with renal involvement. We found no correlation between mtDNA/nucDNA ratio and global disease activity. Mitokine levels, on the other hand, correlated with disease activity, in particular GDF-15 even after adjusting for renal involvement.Conclusion Our findings suggest that lower whole blood mtDNA/nucDNA ratio, a surrogate marker for mitochondrial dysfunction, reflects renal damage, while GDF-15 may also reflect disease activity in SLE. Further studies are needed to assess the clinical value of these markers as predictors for active lupus nephritis.